Resistência ao fogo e atributos funcionais em sementes de leguminosas de campo sujo - Nunes, Jessika da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Fire influences the Cerrado vegetation, affecting the dynamics of plant communities. Fabaceae species are common in these areas, showing seeds with impermeable coats. The impermeability of seed coat is called physical dormancy and factors such as fire-related heat shocks have been recognized to break it in some flammable ecosystems from Australia and the mediterranean. Moreover, for the persistence of those populations at sites influenced by recurrent fires, the seeds should be resistant to high temperatures. Therefore, this study aims to evaluate seed germination and seed traits of legumes from Cerrado open savannas (campo sujo) (8 species: 2 subshrubs, 3 shrubs, 3 trees) in relation to fire. Since the study species occur in an environment with frequent influence of fire, we hypothesized that the seeds would resist the exposure to high temperatures, and would have similar traits, so disturbance acts as an environmental filtering. To analyse the effect of high temperatures we used 5 replicates of 20 seeds/treatment. The following treatments were applied: 100°C for 1 and for 3 minutes, and 200°C for 1 minute, and a control, which was not exposed to any heat shock. After the treatments, the seeds were put to germinate in a germination chamber (27°C, 12h of light) for 30 days, with regular counting of germination, and a viability test (tetrazolium) was performed by the end of the experiment. The results show that all seeds survived the heat shock of 100°C 1', and two species exhibit break of physical dormancy when exposed to the treatment of 100°C 3' (Senna cana and Mimosa kalunga). S. cana had also dormancy breaking when exposed to 200°C. On the other hand, six species had some reduction in germination and/or viability in the treatments considered more severe, 100°C 3' and 200°C. All species had similar traits, with values that classified them as round-shaped (<0.2), and seed mass values ≤0,05g, showing also low water content (<10%)...

O fogo influencia a vegetação do Cerrado, afetando a dinâmica das comunidades vegetais. Espécies da família Fabaceae são frequentes nessas áreas, apresentando sementes com tegumento impermeável. Esta impermeabilidade do tegumento é denominada dormência física, e fatores como choques térmicos relacionados ao fogo são reconhecidos por quebrar tal dormência em ecossistemas inflamáveis da Austrália e de clima mediterrâneo. Além disso, para que as populações destas espécies persistam no local com influência de queimas recorrentes, as sementes devem resistir às altas temperaturas. Portanto, o presente trabalho tem como objetivo estudar a germinação e os atributos funcionais em sementes de leguminosas de campo sujo (8 espécies: 2 subarbustos, 3 arbustos, 3 árvores) em relação ao fogo. Por estarem presentes em um ambiente com frequente influência do fogo, levantamos a hipótese que as sementes resistiriam às altas temperaturas e teriam atributos semelhantes entre si, de forma que o distúrbio agiria como filtro ambiental. Para análise do efeito de altas temperaturas foram utilizadas 5 réplicas de 20 sementes/tratamento. Os seguintes tratamentos foram aplicados: 100°C por 1 e 3 minutos e 200°C por 1 minuto, além de um controle, que não foi exposto ao choque térmico. Após os tratamentos, as sementes foram colocadas para germinar em câmara de germinação (27°C, 12h de luz) durante 30 dias, com contagens regulares da germinação e teste de viabilidade (tetrazólio) ao final do experimento. Além disso, mensuramos atributos funcionais das sementes (20 sementes/indivíduo, de 3-5 indivíduos), como o peso seco (mg), forma (mm), permeabilidade (% da população que ganha peso após 24, 48 e 72h de embebição em água), teor de água (% de água) e germinabilidade (% germinação). Como resultados obtivemos que todas as sementes resistiram ao choque térmico de 100°C 1', e duas das espécies apresentaram quebra de...
Keywords: Ecologia vegetal; Cerrados; Sementes - Dormência; Leguminosa; Germinação; Fogo e ecologia; Comunidades vegetais; Sementes; Queimada; Sementes - Viabilidade